9p24.1 alterations and programmed cell death 1 ligand 1 expression in early stage unfavourable classical Hodgkin lymphoma: an analysis from the German Hodgkin Study Group NIVAHL trial. (14th September 2021) - Gerhard‐Hartmann, Elena; Goergen, Helen; Bröckelmann, Paul J.; Mottok, Anja; Steinmüller, Tabea; Grund, Johanna; Zamò, Alberto; Ben‐Neriah, Susana; Sasse, Stephanie; Borchmann, Sven; Fuchs, Michael; Borchmann, Peter; et al.
Summary: High programmed cell death 1 ligand 1 (PD‐L1) protein expression and copy number alterations (CNAs) of the corresponding genomic locus 9p24.1 in Hodgkin‐ and Reed–Sternberg cells (HRSC) have been shown to be associated with favourable response to anti‐PD‐1 checkpoint inhibition in relapsed/refractory (r/r) classical Hodgkin lymphoma (cHL). In the present study, we investigated baseline 9p24.1 status as well as PD‐L1 and major histocompatibility complex (MHC) class I and II protein expression in 82 biopsies from patients with early stage unfavourable cHL treated with anti‐PD‐1‐based first‐line treatment in the German Hodgkin Study Group (GHSG) NIVAHL trial (ClinicalTrials.gov Identifier: NCT03004833). All evaluated specimens showed 9p24.1 CNA in HRSC to some extent, but with high intratumoral heterogeneity and an overall smaller range of alterations than reported in advanced‐stage or r/r cHL. All but two cases (97%) showed PD‐L1 expression by the tumour cells in variable amounts. While MHC‐I was rarely expressed in >50% of HRSC, MHC‐II expression in >50% of HRSC was found more frequently. No obvious impact of 9p24.1 CNA or PD‐L1 and MHC‐I/II expression on early response to the highly effective anti‐PD‐1‐based NIVAHL first‐line treatment was observed. Further studies evaluating an expanded panel of potential biomarkers are needed to optimally stratify anti‐PD‐1 first‐line cHL treatment.